Analysis of the Implementation of Electronic Medical Records in Community Health Centers - Ade Feryansyah; Sentot Imam Suprapto; Ratna Wardani (GLOBAL HEALTH SCIENCE GROUP, 2025)
The implementation of Electronic Medical Records (EMR) in Community health centers is a strategic step in improving the efficiency and quality of health services. This study aims to analyze the implementation of RME in the West Kotawaringin Regency Health Center with a qualitative descriptive method. This study aims to analyze the application of EMR in the West Kotawaringin Regency Health Center with a qualitative descriptive approach. The research was carried out on three health centers that have implemented EMR, namely the Arsel, Mendawai, and Kumpai Batu Atas Health Centers, in the April-June 2024 period. Data was collected through in-depth interviews and documentation, including aspects of patient registration, data distribution, filling in clinical information, data processing, financing claims, data storage, quality assurance, and EMR content transfer. The 15 respondents consisted of medical personnel and community health centers administration. Data analysis involves three key steps: data reduction, data presentation, and conclusion and verification. The results showed that although the majority of respondents understood the benefits of RME, they faced various obstacles, such as limited technology infrastructure, lack of training for healthcare workers, and system integration problems. The use of EMR has accelerated the service process, but there is still a reliance on manual methods in several stages. In addition, data reporting is often constrained by technical issues and coordination between units. The study findings indicate that while most respondents recognize the benefits of electronic medical records , several challenges hinder optimal implementation. Key obstacles include limited technological infrastructure, insufficient training for healthcare workers, and difficulties in system integration.